Pengaruh Penggunaan Microwave Oven terhadap Proses Sterilisasi Buah Kelapa Sawit - Eli Sovia; Silvi Leila Rahmi; Dewi Fortuna (Fakultas Teknologi Pangan & Agroindustri (Fatepa) Universitas Mataram dan Perhimpunan Teknik Pertanian (PERTETA), 2024)
The sterilization of oil palm fresh fruit bunch (FFB) purpose is to deactivate the lipase enzyme, soften the fruit pulp, and loosen the fruit from the bunch, an important process affecting oil quality. Palm oil mills generally require around 410-455 tonnes of water to produce steam in the sterilization process using boiling vessels and produce 36 tonnes of liquid waste. One way to reduce liquid waste is the development of the use of microwaves. Research on the use of microwaves in palm fruit sterilization will be the basis for developing microwave designs that are suitable for the CPO industry with capacities of hundreds or thousands of tonnes. The aim of this research was to determine the effect of microwave oven sterilization time on the characteristics of oil palm fruit. This research used a completely randomized design with 7 treatment levels and 4 replications to obtain 28 experimental units. The treatment used was sterilization using a boiling vessel (T0) and the sterilization time for oil palm fruit using a microwave oven: 3, 5, 7, 9, 11 and 13 minutes will be analyzed using SPSS at 5% level. Based on the results of the research that has been carried out, it can be concluded that sterilization of oil palm fruit using boiling vessels and microwave ovens have a significant effect on sterilization temperature, water content, yield, Free Fatty Acid, Deterioration of Bleachability Index (DOBI) and carotene. The best treatment is sterilization of oil palm fruit using a microwave oven for 7 minutes with sterilization temperature parameters 94.06ºC, water content 0.55%, yield 17.81%, FFA 0.51%, DOBI 3.88nm and carotene 675.52ppm.